Knowing and doing vocational education and training reform: evidence, learning and the policy process - McGrath, Simon; Lugg, Rosemary (Elsevier, 2012)
Much of VET policy internationally draws on a toolkit that has been seriously questioned for its logic, international relevance and effectiveness by considerable amounts of academic research. Reflecting primarily on our experiences of leading a complex, multi-country policy study, we develop an account that seeks to explore ways in which the apparent incommensurability between academic and policy knowledge can be addressed. This leads on to a broader discussion of key issues of contestation in the debates about knowledge for policy as they relate to international education and development more generally. We consider three key turns in the discourse of international education policy and research: to "governing by numbers", "what works" and policy learning, and ask what happens when these discursive trends travel to Southern and VET contexts. We suggest that this analysis implies that policymakers need both to be more modest and reflexive in their expectations of what knowledge can be mobilised for policy purposes and more serious in their commitment to supporting the generation of the types of knowledge that they claim to value. For international and comparative educators, we stress the importance of being clearer in seeking to shape research agendas; more rigorous in our approaches to research; and better in our external communication of our findings. Given the particular focus of this special issue on VET, we end by reiterating the particular challenge of reawakening research on VET-for-development from twenty years of slumbers.